Perfil imunoistoquímico dos linfomas difusos de grandes células B caninos utilizando-se o método de microarranjo de tecido (TMA) - Silva, Maria Claudia Lopes da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Non Hodgkin lymphomas (LNHs) are the most common hematopoietic tumors of dogs, among which Diffuse Large B Cell Lymphoma (DLBCL) is the most frequent subtype. DLBCLs are tumors composed of lymphoid B cell with a diffuse growth pattern and may present at least five variants. The present work intended to delineate the immunohistochemical profile of canine DLBCL, classify them according to the criteria proposed by WHO (2008); veterinary WHO (2002) and Updated Kiel Classification and also perform the evaluation of the used antibodies on tissue microarray (TMA) method in comparison to conventional histological sections. The immunohistochemical expression of pan B markers (anti CD79a, anti CD20 and PAX-5) was assessed; as well as the determination of proliferation index (Ki-67) and apoptosis (caspase 3) and also the expression of the mutant p53. There were 24 monomorphic centroblastic lymphomas, 4 imunoblastic B and 1 polimorphic centroblastic according to Kiel. That profile is 25 Diffuse Large B Cell Lymphoma/ DLBCL, NOS centroblastic variant and 4 Large Cell Imunoblastic/ DLBCL, NOS imunoblastic variant according to WHO 2002 and 2008 respectively. Immunolabeling was seen in 100%, 75.8% and 58.6% of the cases for CD79a, CD20 and PAX-5 respectively. The immunolabeling median percentage of Ki67 was 45.9% and for caspase-3 it was 10%. The expression of mutant p53 was observed in 16 tumors (55.1%). The analysis of those markers using TMA resulted in identical imunophenotype and significantly similar medians of caspase-3, Ki67 e p53 when compared to conventional sections. In conclusion there was no statistical difference among the histological subtypes regarding proliferation and apoptotic indexes and p53 expression in our samples. Also, TMA is an adequate technique for evaluating imunophenotype, proliferation and apoptotic indexes as well as presence of mutant p53

Os linfomas não Hodgkin (LNHs) são as neoplasias hematopoiéticas mais comuns nos cães, sendo o Linfoma Difuso de Grandes Células B (DLBCL) o subtipo mais frequente. Os DLBCLs são neoplasias formadas por células linfoides B com padrão de crescimento difuso e podem apresentar pelo menos cinco variantes. O presente trabalho teve como objetivos traçar o perfil imunoistoquímico dos DLBCLs dos cães, classificá-los de acordo com os critérios estabelecidos pela WHO (2008), WHO veterinária (2002) e Classificação de Kiel e efetuar a avaliação dos anticorpos utilizados pelo método de microarranjo de tecido (TMA), comparando-o com o corte convencional. Foi avaliada a expressão imunoistoquímica de marcadores pan B (CD79a, CD20 e PAX-5); a determinação dos índices proliferativo (Ki-67) e apoptótico (caspase-3) e também da expressão de p53 mutante. Foram observados 24 linfomas centroblásticos monomórficos, 4 imunoblásticos B e 1 centroblástico polimórfico de acordo com a classificação de Kiel. Este perfil é de 25 Linfomas de Grandes Células B Difusos/ DLBCL, NOS variante centroblástica e 4 Imunoblásticos de Grandes Células /DLBCL, NOS variante imunoblástica, pela WHO de 2002 e 2008, respectivamente. Houve marcação em 100%, 75,8% e 58,6% dos casos para o CD79a, CD20 e PAX-5, respectivamente. A mediana de porcentagem de marcação para o Ki-67 e para a caspase-3 foi de 45,9% e 10%, respectivamente. Já a expressão da proteína p53 mutante foi verificada em 16 tumores (55,1%). A análise destes marcadores utilizando-se o TMA resultou em perfil imunofenotípico idêntico e medianas de caspase-3, Ki67 e p53 significativamente semelhantes quando comparadas com o corte convencional. Concluiu-se que em nossas amostras não houve diferença estatística entre os diferentes subtipos histológicos em relação aos índices proliferativo e apoptótico e expressão da p53. Ainda, o TMA é uma técnica adequada para avaliação do...
Canine diffuse large B cell lymphoma imunohistochemical profile using tissue micoarray (TMA)
Keywords: Cão - Doenças; Imuno-histoquímica; Linfoma; Patologia veterinaria; Análise de microarranjo; Microarray Analysis; Lymphomas